1987
DOI: 10.1021/jm00391a037
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antifungal activity of a series of novel 1,2-disubstituted propenones

Abstract: To find an antifungal agent other than those of the imidazole and triazole series, a new class of 1,2-disubstituted propenones I and II was prepared and tested for antifungal activity. Comparison of the structure-activity relationships showed that the conjugated structure of carbonyl and exomethylene groups in I and II plays an important role in potent antifungal activity. However, it is noteworthy that compounds 53, 54, and 56, which have a hydroxymethyl or methoxymethyl group instead of an exo-methylene grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 1 publication
0
23
0
Order By: Relevance
“…2-Bromoacetophenone and amidinothiourea mixed in ethanol were condensed to provide benzyl guanidine 1 in 87% yield [25]. 2-Bromo-1-(thiophen-2-yl) ethanone was synthesized from the bromination of 1-(thiophen-2-yl)ethanone according to the previously reported procedure [26]. Subsequently, cyclization reaction of benzyl guanidine 1 and 2-bromo-1-(thiophen-2-yl)ethanone was conducted by refluxing the reaction mixtures at 80°C to afford 2-amino-1-thiazolyl imidazole 2 in 62% yield [27].…”
Section: Methodsmentioning
confidence: 99%
“…2-Bromoacetophenone and amidinothiourea mixed in ethanol were condensed to provide benzyl guanidine 1 in 87% yield [25]. 2-Bromo-1-(thiophen-2-yl) ethanone was synthesized from the bromination of 1-(thiophen-2-yl)ethanone according to the previously reported procedure [26]. Subsequently, cyclization reaction of benzyl guanidine 1 and 2-bromo-1-(thiophen-2-yl)ethanone was conducted by refluxing the reaction mixtures at 80°C to afford 2-amino-1-thiazolyl imidazole 2 in 62% yield [27].…”
Section: Methodsmentioning
confidence: 99%
“…This attempt has been made by several researchers [7][8][9]. Earlier studies have reported the use of propenone compounds such as 1-furan-2-yl-3-pyridin-2-yl-propenone (FPP-3) for inflammatory disorders [10], and 1, 2-disubstituted propanones as antifungal agents [11]. The wide range of biological activities of 1,3-diphenyl-2-propen-1-one derivatives has been studied by other researchers [12].…”
Section: Introductionmentioning
confidence: 99%
“…The intermediate adduct 9 extruded nitrogen to form the 2-pyridone 10. These types of pyridones are difficult to obtain by other methods and are of interest for their biological activity [6].…”
Section: Introductionmentioning
confidence: 99%